PAI-1 Plays an Important Role in the Expression of t-PA Activity in the Euglobulin Clot Lysis by Controlling the Concentration of Free t-PA - Urano, Tetsumei; Sumiyoshi, Kenichi; Pietraszek, Michal H; Takada, Yumiko; Takada, Akikazu (Thrombosis and Haemostasis, 1991)
The antigen levels of tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) were assayed in the plasma and in the euglobulin fraction, and their contributions to the euglobulin clot lysis time (ECLT) and t-PA activity were analyzed. Total and free PAI-1 levels in both fractions showed significant positive correlation with ECLT (p <0.001), whereas t-PA antigen level did not have a high correlation coefficient with ECLT. t-PA activity showed significant negative correlation with ECLT (p <0.001) and positive correlation with free t-PA level (p <0.001), which was calculated by the ratio of the concentrations of t-PA-PAI-1 complex and the free PAI-1. Thus free t-PA seems to dissolve the euglobulin clot and its concentration seems to be controlled by the concentration of free PAI-1. These findings were confirmed by the analyses of the effects of C1-inactivator and antibody against t-PA to regular ECLT and kaolin activated ECLT, the latter of which was only inhibited by the addition of C1-inactivator whereas the former was inhibited by anti-t-PA antibody.